Ferrivauxite, a new phosphate mineral from Llallagua, Bolivia. (2nd January 2018) - Raade, G.; Grice, J. D.; Rowe, R.
Abstract: Ferrivauxite, ideally Fe 3+ Al2 (PO4 )2 (OH)3 ·5H2 O, is an oxidized equivalent of vauxite, Fe 2+ Al2 (PO4 )2 (OH)2 ·6H2 O, and forms oxidation pseudomorphs after that mineral. It occurs in association with sigloite and crandallite at the Llallagua tin deposit, Bolivia. It is triclinic, space group P1̄, with a = 9.198(2), b = 11.607(3), c = 6.112(2) Å, α = 98.237(9), β = 91.900(13), γ = 108.658(9)°, V = 609.7(5) Å3, Z = 2. Strongest reflections of the powder X-ray diffraction pattern are [dobs in Å(Iobs )(hkl)]: 10.834(100)(010), 8.682(24)(100), 8.242 (65)(110), 6.018(28)(001), 5.918(23)(1̄10), 5.491 (30)(1̄20), 4.338(26)(200), 2.898 (32)(300). The structure was refined to R1 = 0.0369 for 3244 observed reflections. Twinning occurs on {010}. Ferrivauxite is isotypic with vauxite but with positional disorder of the Fe1 site and some of the oxygen sites. Disorder is also indicated by the infrared spectrum. One of the water molecules in vauxite is deprotonated in conjunction with the oxidation process and becomes a hydroxyl group. Ferrivauxite is translucent to transparent, has a golden brown colour with a pale yellow-brown streak and vitreous lustre. It is brittle with an irregular fracture and shows no cleavage. The Mohs hardness is estimated to be ∼3½ by comparison with vauxite. D(calc.) is 2.39 g cm –3 for the empirical formula Fe 3+ 0.94 Mn0.01 Al1.98 P2.05 O8 (OH)3 · 5H2 O, obtained by electron-microprobe analysis in wavelength dispersive spectroscopy mode. The mineral is optically biaxial negative with α = 1.589(1), β = 1.593(1), γ = 1.596(1); the refractive indices are higher than those of vauxite.